Cournot Competition, Market Size Effects and Agglomeration - Fredrik Gallo (Lund University, School of Economics and Management, Department of Economics, 2005)
We analyse a two-stage location-quantity game with many firms and two regions. We show that the firms will never agglomerate in the same location if transportation is costly between the regions. We also analyse the effects of differences in market size and economic integration on the allocation of industrial activity. For high levels of trade costs firms locate in different regions. Lowering the trade costs beyond a critical level triggers an agglomeration of industry in the larger region. This process of agglomeration is gradual in nature and trade costs have to be successively lowered for a full-scale agglomeration to take place.
Keywords: D43; F12; L13; R30; 330; agglomeration; cross-hauling; market size effects; spatial Cournot competition